Edukasi Penggunaan Obat di bulan Ramadhan sebagai Upaya Penggunaan Obat yang Rasional di Desa Bugel - Irma Susanti; Khusnul Khotimah; Maya Maghfirotur Rohmah; Laela Novita Sari; Ayu Fermiasari; Sahla Ayu Fatmawati; M. Fadlil Al-Hafidz (Jurnal ABDIMAS-HIP Pengabdian Kepada Masyarakat, 2024)
The month of Ramadan is a moment that is eagerly awaited by all Muslims in the world. Ramadan fasting is mandatory for every Muslim, but there is relief for sick people who can cancel it. People who experience health problems can affect the pattern of drug use as usual. It is important to pay attention to changes in the medication use schedule so that it does not affect the effect of the therapy being given or currently being undertaken, so education regarding the use of medication during the fasting month is necessary so that it is rational and ensures that the medication that enters the body provides maximum effectiveness without causing danger or bad effects on the body. The community service methods used are face-to-face lectures, discussions and question and answer methods which was attended by 34 posbindu participants. The results of providing this education show that the level of knowledge of respondents before being given education, namely 60%, is in the sufficient category, while the level of knowledge of respondents after being given education is 100% in the good category. Based on the research results, it can be concluded that the level of knowledge of respondents before and after being given education experienced a significant increase in knowledge with a p value <0.05. Community service activities through providing education can increase respondents' knowledge about the use of drugs during fasting.